Android-Based Practical Work Student Registration Form Application System Design - Aulia Ichsan; Mhd. Zulfansyuri Siambaton; Khairuddin Nasution (Ilmu Bersama Center, 2023)
This system is designed to improve the efficiency of the attendance process through the use of information technology. The system allows students to register for attendance online through an android-based mobile application. Implementation involves developing an application with registration and attendance recording features, as well as student data management. Evaluation involves user feedback to improve performance and functionality. The support of PT PLN (Persero) is very important in the implementation of this system. The hope is that this online attendance system can improve the efficiency, accuracy, and reliability of the attendance process for practical work students at PT PLN (Persero) and provide guidance for other organizations in utilizing information technology.